Identifying injury diagnoses associated with a high probability of admission. (1st March 2011) - Cryer, C; Gulliver, P; de Graaf, B; Davie, G; Langley, J
Abstract : Background: When making international comparisons of non-fatal injury, they are often based on hospital data, and are contaminated by health service effects. One way to reduce this contamination is to make comparisons using a case definition based on diagnoses that have high probabilities of admission. Aim: To identify International Classification of Diseases (ICD) diagnoses associated with a high probability of admission. Method: We identified international collaborators who had access to Emergency Department data whose diagnoses were coded to the ICD. A protocol for data provision was agreed with our collaborators. The submitted data was checked by the New Zealand team and then via liaison with the collaborators. Country-specific results were presented at the ICD 4- character level. Results were also contrasted between countries. Results: The results show that the only injuries with strong evidence for high probabilities of admission, consistently across all collaborating countries, were fractured neck of femur and other femoral fractures (S720, S721, S722 and S723). Other injuries that were potentially consistent with high probabilities, but for which the estimates had wide CIs due to small numbers in some of the collaborators data, included: focal brain injury (S063), traumatic haemopneumothorax (S272), injury of the spleen (S360), liver or gall bladder (S361). Outcome: The information generated by this project will inform all high income countries of those diagnoses that almost always get admitted to hospital. It will also suggest a case definition suitable for making international comparisons.